Réponses

2014-01-31T13:27:31+01:00
1)
6 - 4 ( x - 2 ) =
6 - 4x + 8 =
-4 x +14 =
2 (7 - 2x )

2)
(4x10puiss-3) : (5x10puiss2)   ( les codes : = /  ; ^ = puissance ; * = multiplié)
(4*10^-3) / 5 * 10 ^2 =
4* 10^-3 *10 ^-2 / 5 =
4/5 * 10^-5
si tu as des questions, n'hésite pas.
Je n'ai pas les même résultats, car mon exercice est sous forme de QCM : 6 - 4 ( x - 2 ) = a) 2 x - 4 b) 14 - 4 x c) - 2 - 4 x 4x10puiss-3 / 5x10puiss2 = a) 0.0000008 b) 8x10puiss-6 c) 0.8x10puiss-6
mais si! 14 - 4x et 8 * 10^-6 (= 0.8* 10^-5) = (4/5 *10 ^-5) !